Pengecekan Conformance Modul Proses Keuangan Dengan Process Mining Pada Rumah Sakit Medika Mulia Di Kabupaten Tuban - Harisul Ikrom Amin; Aditya Rachmadi; Nanang Yudi Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The mining process in modelling system of business process serves to know an executed business process in the event log that shows a workflow on the running business processs. The format that must be exist in making the event log of business process are case id, timestamp, and activity, then the event log will be transformed in the form of XML mining model and Petri Net model as well. Moreover, ProM tools is a tool in the process of mining which use the existing plugin in ProM tools compared with existing business processes on the company. It is compared based on the parameters available in ProM tools which is to find the value of fitness and structure then those process are compared. In this case, Medika Mulia Hospital in Tuban Regency has develoed its own ERP system. ERP system in this hospital is used as a system that manages all business processes in the hospital. Before the ERP system is used and implemented, it needs an analysis on the business process which is to examine whether it will be in accordance with the ERP system or not. The method that used by the author of this study is mining process analysis.